Implementing Genre Based Approach in Teaching Reading: A Case Study at Vocational High School Students - Lailatussyifa, Nola Putri; Al Baekani, Abdul Kodir; Hakim, Putri Kamalia (FKIP - Universitas Riau, 2025)
This study explores the implementation of the Genre-Based Approach (GBA) in teaching reading to vocational high school students. Utilizing qualitative research methods, the study examines the stages of GBA, namely Building Knowledge of the Field (BKoF), Modeling of the Text (MoT), and Independent Construction of the Text (ICoT), while skipping the Joint Construction of the Text (JCoT). Findings indicate that interactive discussions during BKoF and the teacher's demonstration of text structures and language features during MoT significantly enhance students' understanding of narrative texts. The transition to ICoT facilitated students' independent text analysis, promoting autonomy and confidence. Student feedback highlights increased engagement and comprehension, particularly due to the interactive and structured nature of GBA. This approach effectively fosters a supportive learning environment, resulting in improved reading skills and a deeper understanding of narrative texts.